Citizen : an American lyric - Rankine, Claudia, 1963- (UK: Penguin books, 2014)
"Claudia Rankine's bold new book recounts mounting racial aggressions in ongoing encounters in twenty-first-century daily life and in the media. Some of these encounters are slights, seeming slips of the tongue, and some are intentional offensives in the classroom, at the supermarket, at home, on the tennis court with Serena Williams and the soccer field with Zinedine Zidane, online, on TV--everywhere, all the time. The accumulative stresses come to bear on a person's ability to speak, perform, and stay alive. Our addressability is tied to the state of our belonging, Rankine argues, as are our assumptions and expectations of citizenship. In essay, image, and poetry, Citizen is a powerful testament to the individual and collective effects of racism in our contemporary, often named 'post-race' society"--From publisher's description.
Includes bibliographical references (pages 167-168).
Keywords: Racism -- United States; United States -- Race relations